Effects of heat exposure and sex on ileal digestibility of amino acids of soybean meal in broiler chickens. - Soleimani Farjam, Abdoreza; Meimandipour, Amir; Azhar, K.; Ebrahimi, Mahdi; Idrus, Zulkifli (Verlag Eugen Ulmer, 2010)
The aim of the present study was to determine the effect of heat exposure (35 vs 21°C) on ileal nitrogen (N) and amino acid (AA) digestibility of soybean meal in broilers. A total of 240 day-old broiler chicks (120 males, 120 females) were housed in battery cages in an environmentally controlled chamber. On day 42, chicks were fed a diet based on soybean meal as sole source of protein following no heat exposure, exposure to 35 ± 1°C for 3 h from day 28 to 42 or exposure to 35 ± 1°C for 3 h from day 35 to 42. Heat exposure significantly (P < 0.05) decreased N and AA digestibility. However, Asp, Glu, Ser, Pro, Trp and Met digestibility were not affected. The least and most affected AA by heat exposure were Met and Tyr, respectively. There was no significant (P > 0.05) effect of sex on N and AA digestibility. In conclusion, these results demonstrated that standardized ileal AA digestibility of soybean meal suppressed under heat exposure by almost 5.5%. Neither 7 nor 14 days of heat exposure induced acclimation and subsequent improvement in AA digestibility. Together, the data indicate that the measurement of feed ingredients ileal digestibility under different environmental conditions merits investigation.